Milestones & Memories: Seventy-Fifth Anniversary, American Agricultural Editors’ Association - Bob Kem (Journal of Applied Communications, 1997)
A review of Milestones & Memories: Seventy-Fifth Anniversary, American Agricultural Editors’ Association, by Wayne E. Swegle and John Harvey, eds.